The Relationship of Self-Disclosure to Relationship Satisfaction in Early Young Adults in Long Distance Relationships - Yizfretty Deslya Sarosija (Universitas PGRI Yogyakarta, 2024)
This research aims to determine the significance of the relationship between self-disclosure and relationship satisfaction in young adults who are in long distance relationships. There were 105 participants in this research using incidental or accidental sampling techniques. The data collection methods used in this research are the self-disclosure scale with the Resived Self-disclosure Scale and the relationship satisfaction scale with the Relationship Assessment Scale (RAS) compiled. he data analysis technique used is the Pearson product moment correlation technique. From the results of data analysis, it was obtained that the correlation coefficient was r = 0.580 and sig was 0.000 (p<0.05), which means that there is a significant positive relationship between self-disclosure and relationship satisfaction in young adults who are in long distance relationships. Where the higher the self-disclosure, the higher the level of relationship satisfaction in young adults who are in long distance relationships. Keywords: self-disclosure, relationship satisfaction, emerging adulthood : long distance relationship